Epidemiology, Mortality and Healthcare Resource Utilization Associated With Systemic Sclerosis-Associated Interstitial Lung Disease in France - Cottin, Vincent; Larrieu, Sophie; Boussel, Loic; Si-Mohamed, Salim; Bazin, Fabienne; Marque, Sébastien; Massol, Jacques; Thivolet-Bejui, Françoise; Chalabreysse, Lara; Maucort-Boulch, Delphine; Jouneau, Stéphane; Hachulla, Eric; et al. (Frontiers in Medicine, 2021)
Objectives: To investigate the clinical characteristics, epidemiology, survival estimates and healthcare resource utilization and associated costs in patients with systemic sclerosis-associated interstitial lung disease (SSc-ILD) in France. Methods: The French national administrative database, the Système National des Données de Santé (SNDS), includes data on 98.8% of the French population, including data relating to ambulatory care, hospitalizations and death. In our study, claims data from the SNDS were used to identify adult patients with SSc-ILD between 2010 and 2017. We collected data on clinical features, incidence, prevalence, survival estimates, healthcare resource use and costs. Results: In total, 3,333 patients with SSc-ILD were identified, 76% of whom were female. Patients had a mean age (standard deviation [SD]) of 60.6 (14.4) years and a mean (SD) individual study duration of 3.9 (2.7) years. In 2016, the estimated overall incidence and prevalence was 0.69/100,000 individuals and 5.70/100,000 individuals respectively. The overall survival estimates of patients using Kaplan–Meier estimation were 93%, 82% and 55% at 1, 3 and 8 years respectively. During the study, 98.7% of patients had ≥1 hospitalization and 22.3% of patients were hospitalized in an intensive care unit. The total annual mean healthcare cost per patient with SSc-ILD was €25,753, of which €21,539 was related to hospitalizations. Conclusions: This large, real-world longitudinal study provides important insights into the epidemiology of SSc-ILD in France and shows that the disease is associated with high mortality, healthcare resource utilization and costs. SSc-ILD represents a high burden on both patients and healthcare services. Clinical trial registration: NCT03858842; https://clinicaltrials.gov/ct2/show/NCT03858842